Halal Marketing Approaches: A Systematic Review of Strategies, Challenges, and Social Implication - Yusran, Husna Leila; Masnita, Yolanda; Ali, Jati Kasuma; Jatunilawati, Yuana (Department of Islamic Economics, IPB University, 2025)
Halal, meaning